THEORETICAL REVIEW OF ISSUES RELATED TO POST-AMPUTATION RECOVERY OF MILITARY PERSONNEL: PSYCHOLOGICAL ASPECT - Kravchenko, Kateryna; Zhalenko, Liliia (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2025)
B a c k g r o u n d . The article presents the findings of a theoretical review conducted to analyze the issues of psychological post-amputation recovery of military personnel. The loss of an extremity is a serious trauma that impacts the mental state of a serviceman, jeopardizes their self-esteem, changes their perception of their bodies, disrupts their future plans and forces them to accept a new reality. Thus, all these factors create the need for high-quality psychological support during the recovery phase. It is worth mentioning that during the recovery phase military personnel encounter numerous emotional difficulties that require comprehensive professional assistance. In particular, they may experience profound feelings of loss, fears about the future, diminished self-esteem, a sense of helplessness, and even depression. Moreover, the process of adapting to new physical limitations and mastering the use of prosthetics are an extremely important and often psychologically draining stage of recovery. Therefore, psychological support during the recovery phase plays a critical role in improving the quality of life and facilitating the social adaptation of military personnel. M e t h o d s . At this stage of the research the authors have relied on theoretical methods, mainly analysis, synthesis, generalization, comparison, and systematization. Strictly scientific and up-to-date references in both Ukrainian and English were analyzed. R e s u l t s . Despite the relevance of the topic further increased by the full-scale invasion taking place on the territory of Ukraine, the relevant research has been strikingly limited in terms of the number of studies dedicated to the topic, specifically the psychological aspect of recovery. Throughout the review the authors were able to identify the possible reasons behind the insufficient attention devoted to this issue, namely: military personnel encountering own psychological barriers, researchers not being mentally ready to work with this category of respondents (military personnel with an amputation), and difficulties encountered while organizing the studies involving military personnel. C o n c l u s i o n s . The theoretical review allowed the authors to classify the psychological aspects of the post-amputation recovery of military personnel into the following categories that require urgent and thorough research – the mental states of military personnel with amputations, the methodology of psychological support provided to military personnel at different stages of the post-amputation recovery, and the professional skills of experts involved in the psychological support of military personnel post amputation.
Keywords: amputation, military personnel – combat veterans, recovery of military personnel, psychological support during the recovery of military personnel